2014
DOI: 10.1371/journal.ppat.1004159
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Focal Adhesion Kinase by Salmonella Suppresses Autophagy via an Akt/mTOR Signaling Pathway and Promotes Bacterial Survival in Macrophages

Abstract: Autophagy has emerged as an important antimicrobial host defense mechanism that not only orchestrates the systemic immune response, but also functions in a cell autonomous manner to directly eliminate invading pathogens. Pathogenic bacteria such as Salmonella have evolved adaptations to protect themselves from autophagic elimination. Here we show that signaling through the non-receptor tyrosine kinase focal adhesion kinase (FAK) is actively manipulated by the Salmonella SPI-2 system in macrophages to promote i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 54 publications
6
118
1
Order By: Relevance
“…However, two previous reports indicated that mTORC1 promotes intracellular replication of the Gram-negative bacterium Salmonella enterica serovar Typhimurium (37,38). These studies demonstrated that intracellular Salmonella avoids autophagic killing by stimulating the recruitment and activation of mTORC1 on vacuoles containing bacteria.…”
Section: Roles Of Mtor and Pkc-␣ In Listeria Entrymentioning
confidence: 95%
“…However, two previous reports indicated that mTORC1 promotes intracellular replication of the Gram-negative bacterium Salmonella enterica serovar Typhimurium (37,38). These studies demonstrated that intracellular Salmonella avoids autophagic killing by stimulating the recruitment and activation of mTORC1 on vacuoles containing bacteria.…”
Section: Roles Of Mtor and Pkc-␣ In Listeria Entrymentioning
confidence: 95%
“…The reactivation and recruitment of mammalian target of rapamycin (mTOR) to SCVs, which occurs following the acute and transient amino acid starvation response that is induced on infection, inhibits the induction of autophagy and possibly provides an escape mechanism for the bacteria 146 . It has been suggested that in macrophages, an unknown SPI-2 effector is involved in the recruitment of focal adhesion kinase to the SCV, which can then activate mTOR through Akt 147 . Furthermore, it is likely that autophagic targeting of damaged or altered SCVs influences antigen presentation, as well as adaptive and autoimmunity, and a deeper understanding of this process should expand our knowledge of chronic human diseases.…”
Section: Induction Of Host Stress Response Pathwaysmentioning
confidence: 99%
“…Furthermore, it has been shown that autophagy acts as a cell-autonomous defense mechanism against intracellular bacteria, contributing to antibacterial immunity by regulating the inflammatory immune response and routing engulfed intracellular bacteria toward lysosomal degradation (12,13). Many pathogens are able to evade autophagy, although the molecular mechanisms at play remain largely uncharacterized (14)(15)(16)(17)(18)(19)(20). Among these pathogens L. pneumophila is known to escape cellular attack by blocking autophagy defenses (21).…”
Section: Significancementioning
confidence: 99%